When a colonoscopy becomes a duodenoscopy: a palliative treatment of a malignant sigmoidoduodenal fistula. (24th May 2013) - Huber, Xaver; Droeser, Raoul A; Bernsmeier, Christine; Kirchhoff, Philipp
Abstract : We report a case of a 63-year-old female patient suffering from cachexy, anaemia and intractable chronic diarrhoea. As an underlying disease, we found a malignant sigmoidoduodenal fistula of a primary adenocarcinoma of the sigma which represents a rare complication of a frequent disease. Despite the theoretical need for a pancreaticoduodenectomy, only a multivisceral en-bloc resection of the small intestine and left adnexa was performed because of bad general and nutritional condition; this case illustrates a successful multimodal treatment with a palliative intention of a locally advanced colon cancer to alleviate clinical symptoms. The further decourse with the fast development of hepatic metastases confirmed this decision.